2020
DOI: 10.1002/adfm.201908788
|View full text |Cite
|
Sign up to set email alerts
|

Poly(cyclodextrin)‐Polydrug Nanocomplexes as Synthetic Oncolytic Virus for Locoregional Melanoma Chemoimmunotherapy

Abstract: Despite the approval of oncolytic virus (OV) therapy for advanced melanoma, its intrinsic limitations that include the risk of persistent viral infection and cost-intensive manufacturing motivate the development of analogous approaches that are free from the disadvantages of virus-based therapies. Herein, reported is a nanoassembly comprised of multivalent host-guest interactions between polymerized paclitaxel (pPTX) and nitric oxide-incorporated polymerized β-cyclodextrin (pCD-pSNO) that through its bioactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 81 publications
0
35
0
Order By: Relevance
“…Moreover, when combined with immunotherapy, different drugs could stimulate distinct anti‐tumor immune populations to accelerate antitumor process. [ 130 ] Thomas and co‐workers [ 131 ] reported a redox and esterase responsive nanoparticle (pPTX/pCD‐pSNO) from the co‐assembly of polymerized paclitaxel (pPTX) and polymerized β‐cyclodextrin with nitric oxide incorporation (pCD‐pSNO). After cellular uptake, the nanoparticles would respond to intracellular chemical environment, leading to the accurate release of PTX at tumor sites and in situ formation of NO.…”
Section: Nanomedicine Boosting Immunogenicity For Immunotherapymentioning
confidence: 99%
“…Moreover, when combined with immunotherapy, different drugs could stimulate distinct anti‐tumor immune populations to accelerate antitumor process. [ 130 ] Thomas and co‐workers [ 131 ] reported a redox and esterase responsive nanoparticle (pPTX/pCD‐pSNO) from the co‐assembly of polymerized paclitaxel (pPTX) and polymerized β‐cyclodextrin with nitric oxide incorporation (pCD‐pSNO). After cellular uptake, the nanoparticles would respond to intracellular chemical environment, leading to the accurate release of PTX at tumor sites and in situ formation of NO.…”
Section: Nanomedicine Boosting Immunogenicity For Immunotherapymentioning
confidence: 99%
“…-cyclodextrin ( CD) is a nontoxic oligosaccharide, the special hydrophilic shell and hydrophobic cavity allow it to serve as modifier to improve the wettability and biocompatibility. CD has been widely used in the field of medicine and food, [17][18][19][20] such as slow-release drug capsules by using the host-guest interaction, the hydrophobic inner core of the CD fits with most of the organic drug molecular size. Introducing CD to PCL endows the hybrid material with ideal action site for drug inclusion to perform drug loading and controlled release.…”
Section: Introductionmentioning
confidence: 99%
“…The important and complex effectiveness of NO in chemotherapy have been proposed by researchers for a long time. [ 31–35 ] Table S1, Supporting Information, summaries the current methods to investigate the possible application of NO in chemotherapy, including vascular permeability, anticancer effect, tumor ECM degradation, reversal of tumor MDR, etc. It can be found that most of the current researches about chemotherapy with NO are limited to some of these functions, and almost no literature studies more than two of the above functions at the same time.…”
Section: Introductionmentioning
confidence: 99%